The Effects of a Novel MEK Inhibitor PD184161 on MEK-ERK Signaling and Growth in Human Liver Cancer - Patrick J. Klein (Neoplasia: An International Journal for Oncology Research, 2006)
The MEK-ERK growth signaling pathway is important in human hepatocellular carcinoma (HCC). To evaluate the targeting of this pathway in HCC, we characterized a novel, orally-active MEK inhibitor, PD184161, using human HCC cells (HepG2, Hep3B, PLC, and SKHep) and in vivo human tumor xenografts. PD184161 inhibited MEK activity (IC50 = 10-100 nM) in a time- and concentrationdependent manner more effectively than PD098059 or U0126. PD184161 inhibited cell proliferation and induced apoptosis at concentrations of ≥ 1.0 µM in a time- and concentration-dependent manner. In vivo, tumor xenograft P-ERK levels were significantly reduced 3 to 12 hours after an oral dose of PD184161 (P< .05). Contrarily, tumor xenograft P-ERK levels following long-term (24 days) daily dosing of PD184161 were refractory to this signaling effect. PD184161 significantly suppressed tumor engraftment and initial growth (P<.0001); however, established tumors were not significantly affected. In conclusion, PD184161 has antitumor effects in HCC in vitro and in vivo that appear to correlate with suppression of MEK activity. These studies demonstrate that PD184161 is unable to suppress MEK activity in HCC xenografts in the long term. Thus, we speculate that the degree of success of MEKtargeted treatment in HCC and other cancers may, in part, depend on the discovery of mechanisms governing MEK inhibitor signaling resistance.